Application of transaction hysteresis effect in modelling institutional nonequilibrium economy - Marina Katkova; Vladimir Markov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
Relevance of the research is caused by the need of modeling institutional nonequilibrium economy taking into account escalating effect of transaction hysteresis. The main aim of the research is to justify the transaction hysteresis effect in development of institutional nonequilibrium economy. Modeling of its development assumes three trajectories of evolution: linear, binary (and linear or primary-nonlinear) and nonlinear. The authors substantiate the choice of the model specification, model parameters decomposition, development dominants estimation. Research methods: the economical and statistical methods providing a combination of qualitative and quantitative aspects of the analysis of a problem; the synergetic approach characterizing the integrated processes in economic development; the genetic method directed on identification of the hereditary mechanism causing the development of institutional nonequilibrium economy; the system approach promoting consideration of institutional nonequilibrium processes in unity with the endogenous and exogenous factors causing their development. Results. The authors determined the conditions of achieving positive externalities of the transaction hysteresis, proposed and substantiated the algorithm of identifying and verifying trajectories of development of institutional nonequilibrium economy to analyze the occurring processes and to forecast their perspective parameters. The need of adaptive, spline and logit modeling of institutional nonequilibrium economy is proved. The paper proves that the transaction hysteresis phenomenon as a limit form of «dependence on a trajectory of the previous development», which proves itself in moderate nonequilibrium economy, assumes the use of modern models of competitive replacement of technologies, and also makes actual the second stage of modeling of institutional nonequilibrium economy: decomposition on a trend and shift-share components.